Modeling different repair configurations of an aluminum plate with a hole - Aabid, Abdul; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (2018)
In this paper, the effect of composite patch placed above a circular hole of a rectangular plate subjected to uniform tensile load was studied. The fundamental idea is to investigate the stress produced by the composite patch on a hole and along the width of the rectangular plate. ANSYS software was used to study the parameter by finite element analysis. The results verified that the composite patch is also effective to change the state of the stress concentration with single and double. Similarly, the positive electric field would decrease stress concentration along the width of the rectangular plate. The results also specified that the reduction of the stress concentration factor (SCF) increases with the decrease of diameter to width ratio (D/W) of a plate for the composite patch.